Basics and Applications in Quantum Optics - Bondani, Maria; Allevi, Alessia; Olivares, Stefano (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Quantum optics has received a lot of attention in recent decades due to the handiness and versatility of optical systems, which have been exploited both to study the foundations of quantum mechanics and for various applications. In this Special Issue, we collect some articles and a review focusing on some research activities that show the potential of quantum optics in the advancement of quantum technologies.